2016
DOI: 10.1016/j.jelechem.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired assemblies and plasmonic interfaces for electrochemical biosensing

Abstract: Electrochemical biosensing represents a collection of techniques that may be utilized for capture and detection of biomolecules in both simple and complex media. While the instrumentation and technological aspects play important roles in detection capabilities, the interfacial design aspects are of equal importance, and often, those inspired by nature produce the best results. This review highlights recent material designs, recognition schemes, and method developments as they relate to targeted electrochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…An example of such a biomimetic system exists in the use of supported lipid bilayers, which are simplified systems that model the cellular membrane, and the constituents of which can easily be altered to allow for specific biomolecular assays to be carried out at the lipid membrane interface. 155,156 There are many ways to construct supported lipid bilayers, 156 including vesicle fusion over a hydrated surface 44,157 or attachment to an underlying surface chemistry, 158 which allows for surface-based analyses, such as SPR, to be conducted. 76,156 Cheng and co-workers developed a benchtop method for creating nanoscale layers of glass on gold SPR substrates via a layer-by-layer deposition and calcination (LbL/calcination) approach, which produced hydrophilic surfaces that were capable of promoting vesicle fusion toward a fluid supported lipid bilayer on an SPR chip.…”
Section: Interface Designmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of such a biomimetic system exists in the use of supported lipid bilayers, which are simplified systems that model the cellular membrane, and the constituents of which can easily be altered to allow for specific biomolecular assays to be carried out at the lipid membrane interface. 155,156 There are many ways to construct supported lipid bilayers, 156 including vesicle fusion over a hydrated surface 44,157 or attachment to an underlying surface chemistry, 158 which allows for surface-based analyses, such as SPR, to be conducted. 76,156 Cheng and co-workers developed a benchtop method for creating nanoscale layers of glass on gold SPR substrates via a layer-by-layer deposition and calcination (LbL/calcination) approach, which produced hydrophilic surfaces that were capable of promoting vesicle fusion toward a fluid supported lipid bilayer on an SPR chip.…”
Section: Interface Designmentioning
confidence: 99%
“…The use of zwitterionic antifouling surfaces consisting of phosphocholines is another example of how naturally occurring chemistries can successfully be used in the design of an SPR sensor. An example of such a biomimetic system exists in the use of supported lipid bilayers, which are simplified systems that model the cellular membrane, and the constituents of which can easily be altered to allow for specific biomolecular assays to be carried out at the lipid membrane interface. , There are many ways to construct supported lipid bilayers, including vesicle fusion over a hydrated surface , or attachment to an underlying surface chemistry, which allows for surface-based analyses, such as SPR, to be conducted. , Cheng and co-workers developed a benchtop method for creating nanoscale layers of glass on gold SPR substrates via a layer-by-layer deposition and calcination (LbL/calcination) approach, which produced hydrophilic surfaces that were capable of promoting vesicle fusion toward a fluid supported lipid bilayer on an SPR chip. These nanoglassified gold sensor surfaces were used in the analysis of membrane bound proteins by SPR and SPRi, with Hinman et al recently utilizing the methods to study the formation of hybrid bilayer interfaces consisting of phosphocholine and synthetic amphiphilic dendrimers . Supported lipid bilayers on nanoglassified SPR chips have been extensively applied for the investigation of water-soluble deep cavitands, which self-incorporate into the bilayer, forming a pocket capable of hosting a wide variety of proteins and functionalized molecules. , Perez et al demonstrated the use of these cavitands embedded within a supported lipid membrane for site-specific polymer growth at this biomimetic interface, enabling the attachment of nonadherent cells and proteins .…”
Section: Interface Designmentioning
confidence: 99%
“…Apart from these fundamentals studies, model lipid membranes have also been used as platforms for other applications, such as lipid-assisted assays and biosensors [8][9][10][11]. In these applications, the resistance and morphological stability in dried or low humidity environments is an important feature.…”
Section: Introductionmentioning
confidence: 99%
“…Many solid-based electrochemical sensing systems combined biomolecules (such as DNA, RNA, peptides, enzymes) as functional connecting “wires” with nanomaterials (such as gold nanoparticles (AuNPs), graphene, quantum dots) as nanoamplification to modify and expand the surface of the electrodes for applications in biosensing, biofuel cells, and logic gate operations. Because the labeled biomolecules were expensive, and one redox label (ferrocene or methylene blue) could only be tagged to one biomolecule, leading to a small electrochemical signal and bioaffinity reduction .…”
mentioning
confidence: 99%
“…With the help of strengths of solid-phase substrates in easy solid−liquid separation and eliminating invalid inputs and verbose outputs, the versatility and universality of solidbased platforms gives a favorable opportunity to realize sensing and computing integration for effectively organizing and regulating logic functions and processes. 22 Many solid-based electrochemical sensing systems combined biomolecules (such as DNA, RNA, peptides, enzymes) as functional connecting "wires" with nanomaterials (such as gold nanoparticles (AuNPs), graphene, quantum dots) as nanoamplification 23 to modify and expand the surface of the electrodes for applications in biosensing, 24 biofuel cells, 25 and logic gate operations. Because the labeled biomolecules were expensive, and one redox label (ferrocene or methylene blue) could only be tagged to one biomolecule, leading to a small electrochemical signal and bioaffinity reduction.…”
mentioning
confidence: 99%